Encoding bacterial colonization and therapeutic modality by wrapping with an adhesive drug-loadable nanocoating. (January 2023) - Luo, Huilong; Wu, Feng; Wang, Xinyue; Lin, Sisi; Zhang, Mengmeng; Cao, Zhenping; Liu, Jinyao
Graphical abstract: Abstract: Microbial therapy has shown remarkable clinical success. However, insufficient colonization of transplanted microbes at the location of interest and the complexity of mechanisms and targets always lead to unpredictable therapeutic responses or even a failed treatment. Here, wrapping with an adhesive drug-loadable nanocoating is reported to encode bacterial colonization and therapeutic modality. Encoded bacteria show universal robust colonization on a wide variety of murine and porcine biointerfaces, ranging from the skin to the mucosae of the intestine, vagina, trachea, and nose. In addition, coating endows bacteria with editable therapeutic modality of carrying different cargoes, including small molecular berberine and doxorubicin as well as macromolecular proteins and antibodies, to enable multimodal therapy. During in vivo studies, following oral ingestion encoded bacteria demonstrate significantly improved intestinal colonization and synergistically enhanced treatment efficacy in two murine models of intestinal infection and colitis. This work discloses that bacterial colonization and modality can be encoded by single-cell coating, proposing a versatile platform for advanced microbial therapy.